Progress on quality management in the German health system - a long and winding road - Wiskow Christiane; Breckenkamp Juergen; Laaser Ulrich (BMC, 2007)
Abstract The interest in quality management in health care has increased in the last decades as the financial crises in most health systems generated the need for solutions to contain costs while maintaining quality of care. In Germany the development of quality management procedures has been closely linked with health care reforms. Starting in the early nineties quality management issues gained momentum in reform legislation only 10 years later. This review summarizes recent developments in medical quality management as related to the federal reform legislation in Germany. It provides an overview on the infrastructure, actors and on the current discussion concerning quality management in medical care. Germany had to catch up on implementing quality management in the health system compared to other countries. Considerable progress has been made, however, it is recognized that the full integration of quality management will require long-term commitment in developing methods, instruments and communication procedures. The most ambitious project at present is the development of a comprehensive comparative quality management system for hospitals at national level, including public reporting. For the time being medical quality management in Germany is dealt with as a technical and professional issue while the aspects of patient orientation and transparency need further advancement.